Recolonization Dynamics of Warm Affinity Halophila nipponica in a Temperate Seagrass Meadow With Zostera marina - Kim, Seung Hyeon; Kim, Young Kyun; Kim, Hyegwang; Lee, Kun-Seop (Frontiers in Marine Science, 2020)
Because Halophila nipponica has only recently been reported in the temperate coastal waters of the northwestern Pacific, the recolonization dynamics of this species have not yet been investigated in temperate seagrass meadows. H. nipponica typically occurs in monoculture or in mixed meadows with Zostera marina, the most abundant seagrass species in this region. In this study, small gaps (0.5 × 0.5 m) were created in a mixed seagrass meadow of H. nipponica and Z. marina at Namhae Island on the southern coast of Korea to compare recolonization dynamics of the two species. Eight gaps were created by carefully removing all seagrass tissues to minimize sediment loss in September 2010. Four gaps were marked using only a steel stake at each corner (un-bordered gaps), while the margins of the other four gaps were blocked to a sediment depth of approximately 20 cm using stainless steel blades to prevent penetration of seagrass rhizomes (bordered gaps) to examine the relative contribution of sexual and asexual reproduction to recolonization. Shoot densities of Z. marina and H. nipponica were measured in the gaps and in natural reference plots to estimate recolonization rates. In the bordered gaps, a few Z. marina seedlings and H. nipponica fragments were observed during winter, but no shoots of either species survived to the end of experiment. In the un-bordered gaps, the density of H. nipponica increased rapidly, with approximately 60% recovery after 2 months and reaching 85% after 10 months through only asexual reproduction via clonal growth. By contrast, recolonization of Z. marina was much slower than that of H. nipponica, with only approximately 25% recovery after 10 months through vegetative growth and recruitment of a few seedlings. Asexual reproduction was the principle reproductive mechanism for the recolonization of both Z. marina and H. nipponica at the study site. According to our results, gaps created naturally in mixed seagrass meadows by high water temperatures or catastrophic events such as typhoons may be primarily recolonized by H. nipponica rather than Z. marina, leading to a change in the seagrass ecosystem structure in the northwestern Pacific under ongoing climate change.